PERAN GURU MEMBENTUK KARAKTER SISWA PADA PEMBELAJARAN IPS DI SMP NEGERI 24 KOTA PONTIANAK - Tripusa, Anita; Mashudi, Mashudi; Aminuyati, Aminuyati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe goals of this research are to find out how teacher's role shape student's character in teaching-learning IPS subject in classroom. The three roles are teacher as: 1) an educator, 2) as the guidance , 3) as an exampler in shaping student's character. The theory used in this research is Mulyasa's theory that stated three roles of teacher which was stated above. The method of this research is descriptive in qualitative form of research. Technique and tools in collection data are observations, interview and documentations. The results of this research are as an educator teacher provides variety lesson plans  and teacher should acquired a profound knowledge in specific field, as the guidance teacher provides helps in learning in the classroom and outside classroom learning activity teacher observes students behavior and fix their mistakes by giving warm admonition and as an exampler teacher obey the school regulations. In conclusion, the good teacher developing good characters in students. Kaywords : Teacher Role, Student Character, IPS Learning